East African odontopygid millipedes 4: A restricted redefinition of the genus Rhamphidarpoides Kraus, 1960, a related new genus, five new species, and notes on solenomere function (Diplopoda; Spirostreptida; Odontopygidae) - Frederiksen, Sara B.; Enghoff, Henrik (Zootaxa, 2015)
Based mainly on morphology of the solenomere, a restricted redefinition of the millipede genus Rhamphidarpoides Kraus, 1960, is given. R. aberdarei (Brolemann, 1920), R. aloysiisabaudiae (Silvestri, 1907), R. alticolus (Brolemann, 1920), R. austrosudanicus n.sp., (South Sudan), R. collinus n.sp., (Kenya), R. cyclopyge (Attems, 1935), R. filigerus (Attems,1938), R. kenyanus (Brolemann, 1920), R. kilimanjaronus (Attems, 1909) n. comb. ex Odontopyge, R. lobiferus (Attems, 1938), R. milobontei Pierrard, 1970, R. pectinatus n.sp., (Kenya), R. regina (Carl, 1909), and R. ruandensis Kraus, 1960, are referred to Rhamphidarpoides in the restricted sense. Raduliverpa n.gen. is described to accommodate R. serpentispina n.sp. (TYPE SPECIES; Tanzania, Kenya), R. mitis n.sp. (Tanzania). R. serrata (Kraus, 1960), n.comb. ex Rhamphidarpoides, and R. sicaria (Attems, 1935) n. comb. ex Prionopetalum. Rhamphidarpe aculeata Attems, 1938, Rhamphidarpe armata Attems, 1938, Rhamphidarpoides bidens Kraus, 1960, Rhamphidarpoides bidenticulatus Pierrard, 1970, and Odontopyge winspearei Silvestri, 1907, are excluded from Rhamphidarpoides and placed incertae sedis.